Sistem Pemantau Patroli Keamanan Gedung Menggunakan RFID Berbasis Komunikasi Long Range (LoRa) - Nurjihan, Shita Fitria; Nixon, Benny; Siahaan, Abelitho; Kusuma, Dandi (Politeknik Negeri Jakarta, 2023)
Patrolling is a proactive activity carried out by moving from one place to another, checking and ensuring area security and order. This is necessary because security officers cannot directly observe the areas they handle. To make patrols more efficient, a building guard patrol monitoring system is needed. The patrol officer's equipment is brought closer to the RFID tags in each room. The LoRa Node in the patrol tool then sends data to Firebase via LoRa Gateway in the form of room name, patrol officer's name, username, time, date and status. Then, the Android application will display data on patrol officers' tapping activity in real-time to prevent fraud while on patrol. The LoRa test results using the LOS (Line of Sight) method reached a maximum distance of 900 m and Non-LOS reached a maximum distance of 200 m. Internet connection on Android applications use VSAT. The average QoS parameter results for the VSAT internet network for throughput are 28.88 KB, packet loss is 0%, and delay is 467,697 ms.